The Effect Of Liquidity And Good Corporate Governance On Financial Distress (Empirical Study Of Food And Beverage Sub-Sector Companies Listed On The Indonesian Stock Exchange For The Period 2017-2021) - Ryviana, Suci Aulia; Krisnawati, Astrie (UNIVERSITAS PAKUAN, 2019)
Every year, Indonesia's food and beverage industry contributes significantly to GDP (Gross Domestic Product) growth. However, it does not rule out the potential of financial distress suffering certain companies. This study looks at the impact of liquidity and good corporate governance on financial distress in food and beverage sub-sector companies listed on the Indonesia Stock Exchange between 2017 and 2021. The purpose of this study was to learn how liquidity, institutional ownership, management ownership, and independent commissioners influence financial distress. The purposive sample strategy was used in this study to get 8 firms that fit the requirements for the 2017-2021 timeframe. Eviews software was utilized for descriptive statistical analysis and panel data regression analysis. According to the hypothesis testing results, liquidity has a significant negative effect on financial distress. Meanwhile, institutional ownership, management ownership, and the presence of independent commissioners do not affect financial distress.